P709 Endoscopic healing and clinical remission after administration of adalimumab to patients with Crohn's disease of the small intestine. (30th January 2023) - Viazis, N; Koustenis, K; Veretanos, C; Mountaki, A; Almpani, F; Tsatsa, A; Trikola, A; Beka, H; Arvanitis, K; Georgiadi, T; Nousias, G; Mylonas, I; et al.
Abstract: Background: In patients with Crohn's disease (CD) localized in the small intestine, endoscopic healing can be assessed by small bowel capsule endoscopy (SBCE). We aimed to investigate the rate of achieving deep remission, i.e. endoscopic healing and clinical remission in patients with CD of the small intestine, after treatment with adalimumab. Methods: Retrospective analysis of prospectively collected data from all patients who were subjected to SBCE in our department from 1/3/2003 to 30/9/2022. Out of the patients who were subjected to the test for the investigation of suspected or confirmed CD of the small intestine we sought those who were treated with adalimumab (originator or biosimilar) and underwent repetitive SBCE at least 24 weeks after the start of treatment. Endoscopic healing was defined as a Lewis score < 350, while clinical remission was defined as Harvey Bradshaw index ≤ 4. Results: During the study period, 102 patients (men/women: 54/48, mean age ± SD: 31.2±14.1 years) were subjected to SBCE before and after administration of adalimumab for the treatment of small intestinal CD. Of these patients, 11 (10.7%) also had extra-intestinal manifestations (arthritis: n=9, erythema nodosum: n=1, uveitis: n=1). After a mean period of 104 weeks (range 24-416 weeks), endoscopic healing was observed in 49 patients (48.0%). All patients who experienced endoscopic healing were also in clinical remission. There was no statistically significant difference in patients with endoscopic healing between those receiving adalimumab originator or biosimilar (36 out of 73, 49.3% vs 13 out of 29, 44.8%, p=NS). Conclusion: Small bowel capsule endoscopy can help us to identify endoscopic healing, which is observed in about half of patients with CD of the small intestine treated with adalimumab.